A Review of Integrated Photonic Devices Using Sb2Se3 - Xiaojun Chen; Jiao Lin; Ke Wang (Advanced Physics Research)
Abstract The silicon photonic technology is a highly promising option for photonic integrated circuits and has attracted intensive interests, particularly since it can utilize complementary metal‐oxide‐semiconductor processing techniques and facilities, thereby realizing high‐density photonic integrations with low‐cost. Unfortunately, the thermo‐optic and the carrier dispersion effects, which are the typical means of tuning silicon photonics devices, bring the drawbacks of high power consumption and large device size due to the relatively weak effect with a small refractive index change and being volatile. For overcoming these drawbacks, phase‐change materials are introduced into silicon photonic devices, where VO2 and Ge2Sb2Te5 are the most commonly used ones. However, the key disadvantage of large loss resulting from them limits further improving the performances of integrated photonic devices. Therefore, Sb2Se3 has seen increasing interests recently in the design of silicon photonic integrated devices, benefiting from the advantages of having extremely low loss over the C‐band and being non‐volatile. In this paper, the trending recent studies about integrated optical devices are systematically reviewed using Sb2Se3, which are classified according to the device function.